Estimates of Repeat Victimization Using the National Crime Victimization Survey - Ybarra, Lynn M. R. (Journal of quantitative criminology, 2002)
Many crime victims experience multiple victimizations over time. Estimating the rate of repeat victimization from a longitudinal survey, however, is difficult because individuals often have missing data for some of the interviews. We use data from the 1996–98 U.S. National Crime Victimization Survey to explore potential effects of missing data on estimated rates of repeat violent victimizations in individuals. We introduce two algorithms for estimating repeat victimization rates, using logistic models to impute values for individuals who have partial data. These models are applied to estimate rates of repeat victimization for all violent crimes, and separately for crimes of domestic violence. Estimates show substantial sensitivity to the form of the model used.